KOMUNITAS STREET PUNK DI KOTA PAYAKUMBUH, SUMATERA BARAT - Fitri, Cica Aulia; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2019)
ABSTRACT This Study aims to investigate and explain about the bacground someoneis  joining with Street Punk Comunity Payakumbuh and the meaning behind the style they showing. The approach used in this study was descriptive exploratory and use subculture theory from Dick Hebdige with analysis semiotika Roland Barthes. Based on the result of the field reseach, its found five background is the reason why someone joining with Street Punk Comunity which is family problem, hight solidarity, looking for freedom of life, invitation friend, and media infuence. Meaning of they look style and life style which different from general public which result the subculture in Payakumbuh society.   Keywords: Subculture, Street Punk, Punk Payakumbuh